Retrocaval Right Ureter: A Very Rare Congenital Anomaly Successfully Repositioned Antecavally - Hamal, Bhairav K; Thapa, Ganesh; Karmacharya, B G (Medical Journal of Shree Birendra Hospital, 2003)
Retrocaval Right Ureter: A Very Rare Congenital Anomaly Successfully Repositioned Antecavally